Zoning of air quality index (PM(10) and PM(2.5)) by Arc-GIS for Khorramabad city, Iran - Kianisadr, Maryam (Data Brief, 2018)
Nowadays in many countries, air pollution is one of the major issues affecting human health. Among the various air pollutants particulate matters are mainly present in ambient air pollution. The purpose of this study was to measure the concentration of particulate matter (PM) (namely PM(2.5) and PM(10)) and to conduct zoning via GIS software in Khorramabad city (Summer – 2017). According to the findings, the average concentrations of PM(2.5) in July, August and September were 100.1, 116.3, and 199.8 μg/m(3), respectively. Furthermore, the average concentrations of PM(10) in July, August and September were 199.8, 215.7, and 190.8 μg/m(3), respectively. The findings of this study also indicated that due to continuous dust storms,particularly in recent years, the air pollution status in Khorramabad was not suitable that can adversely affect public health.